ETHICAL AND POLITCAL QUALITY OF EPIDEICTIC RHETORIC IN ANCIENT GREECE - Tuszyńska, Krystyna (Porównania, 2015)
Originating from the Greek source, a Latin definition of the orator is vir bonus dicendi peritus and rhetoric itself is ars bene dicendi. This particularly calls for an explanation of the words bonus and bene. Bonus has as much reference to the person of the speaker as it has to the competence in artistic persuasion. In my article I will concentrate on the meaning of bene and bonus from the point of view of the use of the language as a means of communication. The scope of the usage of speech is connected with the common wealth according to which public life and its political and ethical conditions are moulded. The sense of purpose on the other hand lies in the duty of the orator to persuade the audience, to make them believe they have been persuaded successfully. All this becomes possible thanks to the orator’s use of invention and of artificial technique, and to him being perceived as a good man by the audience, where ‘good’ should be understood in both moral and aesthetic terms. Aristotle lays emphasis on three elements: (1) the technique in the arguments of the speech, (2) the ethos of the orator and (3) the pathos produced by the orator in the listeners. In this way Aristotle connects the art of persuasion and dialectics with ethical studies (1356 a 25). For the philosopher, the man is zoon politikon, and the art of rhetoric arises from the necessity of human agreement, the consensus. Because ethos is for Aristotle a vehicle for argumentation, the orator has to produce his ethos all the time during the speech. Aristotle divides rhetoric into three genres: deliberative, forensic and epideictic. In epideictic rhetoric the listener is only a spectator (theoros) and a judge (krites) of the orator’s talent. In my article I would like to prove that epideictic rhetoric, considered a kind of show or theatrical performance, was also a vehicle for many ethical and political qualities. I am going to analyze four speeches of three Ancient orators: Gorgias, Isocrates and Dio of Prusa and ask questions about the nature of epideictic rhetoric, about its capacity and origin. In my opinion thorough research and a rethink-ing of the term ‘epideictic genre’ are needed.